Experimental and Computational Evaluation of a Sodium-Rich Anti-Perovskite for Solid State Electrolytes. Issue 10 (4th August 2016) - Nguyen, Han; Hy, Sunny; Wu, Erik; Deng, Zhi; Samiee, Mojtaba; Yersak, Thomas; Luo, Jian; Ong, Shyue Ping; Meng, Ying Shirley
Abstract : In this study we experimentally investigated the effects of two processing techniques on the sodium-rich anti-perovskite, Na3 OBr; namely, conventional cold pressing (CP) and spark plasma sintering (SPS). We demonstrated that the electrolyte can be synthesized via a single-step solid state reaction. We compared the CP and SPS processed samples using XRD, SEM, and EIS. From these analyses it was found that SPS reduced Na3 OBr's interfacial impedance by three orders of magnitude, which translated into an increase in the overall ionic conductivity and a reduction in the activation energy, from 1.142 eV to 0.837 eV. DFT was used to probe the mechanisms for ionic transport in Na-rich Na3 OBr. The formation energies of ion diffusion-facilitating defects in Na3 OBr were found to be much higher compared to the lithium-rich anti-perovskites (LiRAP), which can explain the difference in overall ionic conductivity between the two.